Perceptions of ICU Care Following Do-Not-Resuscitate Orders: A Military Perspective - Sydney E. Dishman, BS; Kathryn E. Driggers, MD; Laura S. Johnson, MD, FACS; Cara H. Olsen, MS, DrPH; Andrea B. Ryan, RN, MSN; Melissa M. McLawhorn, RN, BSN; Kevin K. Chung, MD, FCCM (Critical Care Explorations)
Objectives:. Although do-not-resuscitate orders only prohibit cardiopulmonary resuscitation in the case of cardiac arrest, the common initiation of this code status in the context of end-of-life care may lead providers to draw premature conclusions about other goals of care. The aim of this study is to identify concerns regarding care quality in the setting of do-not-resuscitate orders within the Department of Defense and compare differences in perceptions between members of the critical care team. Design:. A cross sectional observational study was conducted. Setting:. This study took place in the setting of critical care within the Department of Defense. Subjects:. All members of the Uniformed Services Section of the Society of Critical Care Medicine were invited to participate. Interventions:. A validated 31-question survey exploring the perceptions of care quality in the setting of do-not-resuscitate status was distributed. Measurements and Main Results:. Exploratory factor analysis was used to categorically group survey questions, and average factor scores were compared between respondent groups using t tests. Responses to individual questions were also analyzed between comparison groups using Fisher exact tests. Factor analysis revealed no significant differences between respondents of different training backgrounds; however, those with do-not-resuscitate training were more likely to agree that active treatment would be pursued (p = 0.024) and that trust and communication would be maintained (p = 0.005). Although 38% of all respondents worry that quality of care will decrease, 93% agree that life-prolonging treatments should be offered. About a third of providers wrongly believed that a do-not-resuscitate order must be reversed prior to an operation. Conclusions:. Although providers across training backgrounds held similar concerns about decreased care quality in the ICU, there is wide belief that the routine and noninvasive interventions are offered as indicated. Those with do-not-resuscitate training were more likely to believe that standards of care continued to be met after code status change.